Uma trajetória das narrativas híbridas de história e ficção infantil e juvenil no Brasil: as ressignificações do passado como vias de descolonização na formação leitora - Santos, Vilson Pruzak dos (2023)
Children's and young adult literature was not always seen as an art capable of emancipating the reader in formation, but rather as a pedagogical instrument, produced to teach, moralize and equip the developing subject. However, it is known that concomitantly with this, other literary productions for children and young adult emerged and with them imagination, fantasy, and the possibility of analyzing the world and oneself. In this sense, we observed a literary current that we consider relevant to the formation of the literary reader in development: the hybrid literature of history and fiction for children and young adult. Thus, this research with literature for students in reading training stems from our performance as teachers and from the interests of the Research Group "Reframing of the past in America: processes of reading, writing and translation of hybrid genres of history and fiction - paths to decolonization". This thesis seeks to establish the systematization of a trajectory of hybrid literature of history and fiction for children and young adults in Brazil, as Fleck (2017) did regarding the historical novel aimed at the adult audience. For this, we take as theoretical support the notes of Candido (2006), Lajolo; Zilbermann (2009), Cademartori (2010), Andruetto (2012), among others. Regarding the hybrid productions of history and fiction in Brazilian children's and young adult literature, the sparse information by Coelho (2010) and Luft (2011) are proponents of this. In a larger scope of hybrid productions, we rely on assumptions by Fleck (2007; 2017) that establish the trajectory of the historical novel as a hybrid genre for adult audiences. Anchored in Fleck's (2017) proposal, we conducted a comparative study of the productions of this genre within Brazilian children's and young adult literature, seeking to bring them closer to the latter modality established in the aforementioned studies. This enabled us to analyze the hybrid literature of history and children's and young adult fiction in Brazil and to establish its trajectory. To emphasize the dichotomous view of these narratives, we analyze a significant amount of fiction books according to the groups, phases and modalities that our study allowed us to establish. As results, we found that this hybrid literature in Brazil has been growing, constituting a trajectory that evidences, nowadays, two groups of narratives: uncritical and critical ones; three phases: uncritical establishment/to the critical transaction; the critical/mediation implementation; the critical consolidation; the three modalities: traditional/uncritical, critical/mediation and critical with tendency to deconstruction. Such narratives reveal themselves as a possibility to bring children and young readers critically closer to official narratives, allowing them to reframe their past by filling the gaps left by the hegemonic historiographic discourse, forming literary readers towards decolonization by the reading of decolonial aesthetics projects.